2004
DOI: 10.1158/1078-0432.ccr-04-0902
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antiangiogenic and Androgen Deprivation Therapy for Prostate Cancer

Abstract: Purpose: Androgen ablation therapy leads to mild regression or stabilization of prostate cancer, followed by progression to the fatal androgen-independent state. Whereas androgen ablation diminishes tumor angiogenesis by suppressing vascular endothelial growth factor (VEGF) production, androgen-independent disease is marked by androgen-independent VEGF expression. We examined combined androgen ablation and inhibition of VEGF signaling in an androgen-sensitive human prostate cancer xenograft model (LNCaP) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Thus, targeting the event of angiogenesis by specific antiangiogenic compounds for antitumor effects requires identification of an optimal stage of tumor growth for therapeutic intervention. Many of the preclinical animal studies validating antiangiogenic drugs, recombinant factors, and gene transfer approaches have been done in immunodeficient animals (23)(24)(25)(26). Despite promising results, in these models, the kinetics of implanted tumor growth and the relevance of cell lines studied to the pattern of primary growth and spontaneous progression of human tumor are highly limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, targeting the event of angiogenesis by specific antiangiogenic compounds for antitumor effects requires identification of an optimal stage of tumor growth for therapeutic intervention. Many of the preclinical animal studies validating antiangiogenic drugs, recombinant factors, and gene transfer approaches have been done in immunodeficient animals (23)(24)(25)(26). Despite promising results, in these models, the kinetics of implanted tumor growth and the relevance of cell lines studied to the pattern of primary growth and spontaneous progression of human tumor are highly limited.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of tumor grade at these time points was determined to be >80%. For treatment studies, 22 mice were included for sacrifice at each time point (12,18,24,28, and 32 weeks; 110 mice in total) for pathologic evaluation, and 14 mice were included for end point survival. There were three time points for treatment with rAAV-GFP and rAAV-(E+A) namely 5, 10, and 18 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that prostate blood vessels are dependent on signaling through VEGFR2, and also likely EGFR, present on prostate blood vessels (11,21,25). These effects were anticipated as previous studies have shown that this compound slows growth of s.c. transplanted human prostate cancer cell lines, such as the PC3 and LnCaP, principally by inhibiting angiogenesis (31)(32)(33). Direct effect mediated by the VEGFR2 and EGFR present on the AT-1 cells (and possibly also RET kinase; ref.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings in the orthotopic model, ZD6474 was more effective than castration in inhibiting growth of s.c. transplanted, androgen-sensitive human LnCaP cells (32). This discrepancy is, however, anticipated as the castration response in s.c. LnCaP tumors may be suboptimal as such tumors are not supported by an androgen-regulated stroma and vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical castration in mice bearing LNCaP tumors arrests tumor growth (11). However, this antitumor effect of androgen ablation is temporary.…”
Section: Discussionmentioning
confidence: 99%